STRATEGI DIPLOMASI EKONOMI INDONESIA DALAM MEMPERTAHANKAN KEBIJAKAN HILIRISASI NIKEL PASCA-PUTUSAN WTO DS592 - Michael Hernan Otniel; Nurbani Adine Gustianti (Smart Education, 2026)
Abstract: This study examines Indonesia's layered economic diplomacy strategy in maintaining its sovereign nickel downstreaming policy following the adverse World Trade Organization (WTO) DS592 ruling. Utilizing a qualitative approach with a descriptive-analytical design, this research evaluates the pivotal timeline of 2022–2026 to capture post-dispute dynamics, institutional adaptations, and domestic governance digitalizations. Data were gathered through documentary research from official WTO dispute archives, ministerial performance reports, and credible macroeconomic publications. The findings demonstrate that Indonesia successfully protected its industrial policy space from external interventions by synergizing three diplomatic pillars: leveraging multilateral institutional paralysis through tactical legal maneuvers (